Silver Distribution and Release from an Antimicrobial Denture Base Resin Containing Silver Colloidal Nanoparticles - Monteiro, Douglas Roberto [UNESP]; Gorup, Luiz Fernando; Takamiya, Aline Satie [UNESP]; de Camargo, Emerson Rodrigues; Ruvolo Filho, Adhemar Colla; Barbosa, Débora de Barros [UNESP] (Wiley-Blackwell, 2012)
Purpose: The aim of this study was to evaluate a denture base resin containing silver colloidal nanoparticles through morphological analysis to check the distribution and dispersion of these particles in the polymer and by testing the silver release in deionized water at different time periods.Materials and Methods: A Lucitone 550 denture resin was used, and silver nanoparticles were synthesized by reduction of silver nitrate with sodium citrate. The acrylic resin was prepared in accordance with the manufacturers' instructions, and silver nanoparticle suspension was added to the acrylic resin monomer in different concentrations (0.05, 0.5, and 5 vol% silver colloidal). Controls devoid of silver nanoparticles were included. The specimens were stored in deionized water at 37 degrees C for 7, 15, 30, 60, and 120 days, and each solution was analyzed using atomic absorption spectroscopy.Results: Silver was not detected in deionized water regardless of the silver nanoparticles added to the resin and of the storage period. Micrographs showed that with lower concentrations, the distribution of silver nanoparticles was reduced, whereas their dispersion was improved in the polymer. Moreover, after 120 days of storage, nanoparticles were mainly located on the surface of the nanocomposite specimens.Conclusions: Incorporation of silver nanoparticles in the acrylic resin was evidenced. Moreover, silver was not detected by the detection limit of the atomic absorption spectrophotometer used in this study, even after 120 days of storage in deionized water. Silver nanoparticles are incorporated in the PMMA denture resin to attain an effective antimicrobial material to help control common infections involving oral mucosal tissues in complete denture wearers.
Keywords: Acrylic resin; nanocomposite; polymethylmethacrylate; silver